LEAF-SPECIFIC ANTISENSE INHIBITION OF STARCH BIOSYNTHESIS IN TRANSGENIC POTATO PLANTS LEADS TO AN INCREASE IN PHOTOASSIMILATE EXPORT FROM SOURCE LEAVES DURING THE LIGHT PERIOD - Sonnewald, Uwe; et al. (Plant and Cell Physiology, 1995)
In an attempt to study the importance of starch synthesis in leaves with respect to sink-source interactions, we investigated daily turnover of carbohydrates in leaves of transgenic potato plants inhibited for ADP-glucose pyrophosphorylase (AGPase). Down-regulation of AGPase has been performed using two different promoters: the near-constitutive CaMV 35S promoter, and the ST-LS1 promoter which is active in photosynthetic cells only. Residual AGPase activity in leaves was between 6 and 30% in individual transformants as compared to wild-type potato plants. We found that: (i) photosynthesis is not significantly altered relative to wild-type plants; (ii) levels of starch are markedly reduced in leaves of transgenic plants; (iii) levels of soluble sugars and malate are largely unaffected by the inhibition of AGPase; (iv) the reduction of starch synthesis leads to a higher portion of assimilated carbon being transported from leaves to sink tissues during the light period; (v) altered leaf export characteristics do not change tuber yield under greenhouse conditions. Collectively, these data demonstrate a striking flexibility of the potato plant with respect to day/night rhythms of carbon export from leaves and utilization by the major storage sinks, i.e. developing tubers.
Keywords: ADP-GLUCOSE PYROPHOSPHORYLASE (EC 2.7.7.27); ANTISENSE INHIBITION; ASSIMILATE EXPORT; DAY NIGHT RHYTHM; SOLANUM TUBEROSUM; STARCH SYNTHESIS